Comparison of rice lines derived through anther culture and the pedigree method in relation to blast (Pyricularia grisea Sacc.) resistance - Martínez Racines, César Pompilio; Correa Victoria, Fernando J.; Amézquita, María Cristina; Tulande Valencia, Edgar; Lema, G; Zeigler, Robert S. (Springer, 1996)
Crosses were made between Fanny (highly susceptible to blast) and 11 cultivars differing in blast resistance. Using the pedigree method (PM) segregating generations were evaluated and selected for blast resistance. Via anther culture (AC), doubled-haploids were obtained from F1 plants and from F2 blast-susceptible plants. Pedigree and anther culture-derived lines were planted together and evaluated for blast resistance under rainfed conditions at the Santa Rosa Experiment Station, Villavicencio, Colombia. The principal objective was to compare PM and AC in terms of their efficiency in producing rice lines resistant to blast. Results of a stratified analysis showed an association between method and blast resistance. Results of the logit-model analysis showed that AC produced a significantly (P=0.0001) higher proportion of lines with initial blast resistance (leaf- and neck-blast reaction ?4) than did PM across all cross types. Stable blast resistance was assessed based on field performance over 3 years. AC was superior to PM in generating stable resistance for only some cross types. Consequently, with a few exceptions, AC can be used as effectively as PM to develop rice cultivars resistant to blast, with savings in time and labor. Additionally, blast-resistant lines were obtained either by the pedigree method or by anther culture from crosses between blast-susceptible cultivars (Fanny/CICA4 and Fanny/Colombial). This excludes somaclonal variation as a possible mechanism responsible for this resistance and suggests that a recombination of minor genes could have occurred and was fixed through either method. However, the stability of the resistance was greater in pedigree-derived lines. The implications of these findings for rice blast-resistance breeding are discussed.